1996
DOI: 10.1007/bf02088755
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on natural and delayed healing of experimentally-induced gastric ulcers in rats

Abstract: This study aimed to investigate the effect of age on natural ulcer healing and delayed ulcer healing induced by nonsteroidal antiinflammatory drugs, using a rat model. Gastric ulcers were induced in young, adult, and aged rats using serosal or mucosal (kissing ulcers) application of acetic acid. Rats were treated with indomethacin 1 mg/kg/day subcutaneously or vehicle for two weeks. Ulcers were assessed by macroscopic and histological measurements of ulcer size. Ulcer induction was affected by age. Aged rats d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Penney et al 23) examined whether or not age exerts an influence on development and natural or delayed healing of acetic acid ulcers in rats. Penney concluded that there were age-related differences in the development of gastric ulcers, but no age-related differences in natural and indomethacindelayed ulcer healing.…”
Section: Type 3 Ulcer Modelmentioning
confidence: 99%
“…Penney et al 23) examined whether or not age exerts an influence on development and natural or delayed healing of acetic acid ulcers in rats. Penney concluded that there were age-related differences in the development of gastric ulcers, but no age-related differences in natural and indomethacindelayed ulcer healing.…”
Section: Type 3 Ulcer Modelmentioning
confidence: 99%
“…Gastric ulceration induced by acetic acid applied either to the serosa or to the mucosa showed no consistent differences in ulcer size or in ulcer healing in Sprague-Dawley rats aged two to three months, 11 to 12 months or 23 to 24 months (29). In this study, even the administration of indomethacin failed to alter the healing rate of older animals any more than in the younger animals (29). Similarly, Tsukimi and Okabe (28) showed no changes in the healing of gastric ulcers in older rats.…”
Section: Pathophysiologymentioning
confidence: 82%
“…Several studies have not shown an increase in ulcer size after application of injurious agents in older rodents compared with younger rodents (27,28). Gastric ulceration induced by acetic acid applied either to the serosa or to the mucosa showed no consistent differences in ulcer size or in ulcer healing in Sprague-Dawley rats aged two to three months, 11 to 12 months or 23 to 24 months (29). In this study, even the administration of indomethacin failed to alter the healing rate of older animals any more than in the younger animals (29).…”
Section: Pathophysiologymentioning
confidence: 94%
“…In a previous study, we examined the effect of age on natural ulcer healing and on delayed ulcer healing induced by chronic dosing with indomethacin 1 mg/kg per day 30 . Aged and mature animals showed no reduced capacity for natural ulcer healing.…”
Section: Discussionmentioning
confidence: 99%